2023
DOI: 10.3389/fpubh.2023.1146059
|View full text |Cite
|
Sign up to set email alerts
|

Protection of hybrid immunity against SARS-CoV-2 reinfection and severe COVID-19 during periods of Omicron variant predominance in Mexico

Abstract: BackgroundWith the widespread transmission of the Omicron SARS-CoV-2 variant, reinfections have become increasingly common. Here, we explored the role of immunity, primary infection severity, and variant predominance in the risk of reinfection and severe COVID-19 during Omicron predominance in Mexico.MethodsWe analyzed reinfections in Mexico in individuals with a primary infection separated by at least 90 days from reinfection using a national surveillance registry of SARS-CoV-2 cases from March 3rd, 2020, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Boosters also play a vital role in delaying reinfections, even for those with previous breakthrough cases. Our findings align with recent studies on hybrid immunity ( 20 ) and emphasize the importance of regular booster shots for effective virus control; as they have a better effect of delaying symptomatic infection than a primary series alone. However, given the complexity of infection risk, determining an optimal vaccination schedule based solely on these findings is challenging.…”
Section: Resultssupporting
confidence: 90%
“…Boosters also play a vital role in delaying reinfections, even for those with previous breakthrough cases. Our findings align with recent studies on hybrid immunity ( 20 ) and emphasize the importance of regular booster shots for effective virus control; as they have a better effect of delaying symptomatic infection than a primary series alone. However, given the complexity of infection risk, determining an optimal vaccination schedule based solely on these findings is challenging.…”
Section: Resultssupporting
confidence: 90%
“…Among individual KABs, the strongest association with non-vaccination was observed in respondents who disagreed with the statement ‘My child needs to be vaccinated against COVID-19 even after infection.’ This aligns with prior research indicating a decreased willingness to vaccinate post-COVID-19 recovery [45] . Despite evidence showing that hybrid immunity—resulting from both infection and vaccination—substantially lowers the risk of severe reinfection compared to immunity from previous infection alone [46] , [47] , only 63 % of our respondents acknowledged the importance of vaccination post-infection. By March 2023, a significant portion of the Canadian population had experienced COVID-19 infection [48] .…”
Section: Discussionmentioning
confidence: 63%
“…There was a significant increase in the SARS‐CoV‐2 reinfection rate before and during the Omicron variant period (0.8% vs. 4.3%; p < 0.001) 16 . Another study conducted in Mexico identified a reinfection rate of 3.1% during the Omicron predominance period 17 . According to the latest national surveillance data in Singapore, the incidence of Omicron BA.4 or BA.5 was 7.7−78.3/million PD, while the incidence of Omicron XBB reinfection ranged from 509 to 1854/million PD, depending on the individual's vaccination status and previous infected lineage (Table 1).…”
Section: How Often Does Reinfection Occur?mentioning
confidence: 93%
“… 16 Another study conducted in Mexico identified a reinfection rate of 3.1% during the Omicron predominance period. 17 According to the latest national surveillance data in Singapore, the incidence of Omicron BA.4 or BA.5 was 7.7−78.3/million PD, while the incidence of Omicron XBB reinfection ranged from 509 to 1854/million PD, depending on the individual's vaccination status and previous infected lineage (Table 1 ). 18 It is worth noting that Ciuffreda's study did not report the specific incidence, but found that BA.5 had the highest reinfection rate compared to other lineages, including BA.1, BA.2, and BA.4.…”
Section: How Often Does Reinfection Occur?mentioning
confidence: 99%